2005
DOI: 10.1111/j.1467-789x.2005.00173.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of obesity in Korea

Abstract: During the past decade, obesity has substantially increased in Korea, and this is leading to dramatic increases in complications such as type 2 diabetes. In this review, we discuss the past and the current situation of obesity in Korea based on the national health and nutrition surveys of 1995, 1998, and 2001. Because Korea is geographically isolated with relatively few migrants and has a low level of genetic heterogeneity, this report demonstrates the impact of environmental factors on the development of obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
119
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(127 citation statements)
references
References 0 publications
7
119
0
1
Order By: Relevance
“…However, in the present were found no significant differences in body fat mass in either the experimental or control group, probably indicating that exercise for at least 8 weeks, rather than 4 weeks, is essential for the decrease of body fat mass. This would corroborate the study by Kim et al 2) , who reported that decreases in body fat mass appeared after exercising for at least 8 to 16 weeks.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, in the present were found no significant differences in body fat mass in either the experimental or control group, probably indicating that exercise for at least 8 weeks, rather than 4 weeks, is essential for the decrease of body fat mass. This would corroborate the study by Kim et al 2) , who reported that decreases in body fat mass appeared after exercising for at least 8 to 16 weeks.…”
Section: Discussionsupporting
confidence: 82%
“…In many studies, obesity is identified as the worst chronic and progressive disease. Not only in Western society but also in South Korea, the number of obese men and women has rapidly increased at the rate of 1.3% per year from 1998 to 2001 2) . Obesity is becoming a dangerous problem that increases health risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical characteristics of individuals with type 2 diabetes in Korea have different features compared with those in Western countries [14][15][16]. With rapid socioeconomic progress, the prevalence of type 2 diabetes has markedly increased in Korea and is now similar to that in Western countries [17,18]. Of the community-based epidemiological studies reporting the prevalence of diabetes and its risk factors in Korea, the Committee of the Korean Diabetes Association on the Diagnosis and Classification of Diabetes Mellitus selected four recent studies (1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000) with complete datasets of OGTT results: the Yonchon study [19,20], the Chongup study [21], the Mokdong study [22], and the Ansan study [8].…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] There is an increasing body of evidence for obesity epidemic from many other countries and regions as well, including Europe, 8 Latin America, 9 Australia 10 and Asian countries. [10][11][12][13][14][15][16] Obesity has already become a global health problem. Obesity and overweight contribute significantly to morbidity and mortality and account for a significant percentage of overall health-care costs.…”
Section: Introductionmentioning
confidence: 99%